Synergizing QCC and PDCA Approaches to Foster Kaizen Practices in Wingbox Production at Karoseri - Sumasto, Fredy; Syaeful, Muhamad Eryl Saputra; Solih, Edwin Sahrial; Suroso, Finna; Paramita, Astriyani Sandya (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
This research applies the Quality Control Circle (QCC) method and the PDCA (Plan-Do-Check-Action) approach to overcome problems in hydraulic cylinder bracket mounts in a manufacturing company. At the "Plan" stage, a defect classification analysis, matrix diagram for problem classification, analysis of existing conditions, setting quality, cost, and morale targets, as well as Why-Why and 5W+1H analysis were conducted. At the "Do" stage, the cylinder bracket mounts was redesigned using UNP 5.4 material as a solution to the existing problems. At the "Check" stage, measurements of the improvement results were made to ensure the achievement of the planned targets, including the reduction of damage frequency and repair costs. The results of overcoming the problem of broken hydraulic cylinder bracket mounts showed a decrease in complaints during the 2-month period after implementation. The application of the QCC method and PDCA approach not only effectively addressed the problem, but also increased customer confidence, company sustainability, and worker morale. The next step is “Action” stage to ensure process continuity by standardizing through the creation of operation standards for the manufacture and installation of hydraulic cylinder bracket mounts. As a result, the material change from SPHC 6.0 to UNP 5.4 successfully resolved the damage problem and eliminated complaints within two months after implementation. After implementation, the company can reduce the cost expense of repair by IDR 1,413,510. This success had a positive impact on customer confidence, cost efficiency, and worker morale.